Correction: Obesity and risk of female reproductive conditions: A Mendelian randomisation study. - Samvida S Venkatesh; Teresa Ferreira; Stefania Benonisdottir; Nilufer Rahmioglu; Christian M Becker; Ingrid Granne; Krina T Zondervan; Michael V Holmes; Cecilia M Lindgren; Laura B L Wittemans (PLoS Medicine, 2022)
[This corrects the article DOI: 10.1371/journal.pmed.1003679.].